Modeling and analysis of the impact of smog pollution on the training effect of intensive sports - Han. X. (Caribbean Journal of Science, 2019)
Detioration of air pollution and the frequent occurrence of smog pollution, high-intensity sports training will seriously damage the functions of various organs and body systems, and at the same time affect the training effect. For high-intensity sports training, while actively coping with the impact of bad weather, we should also take effective measures to improve training places, scientifically and rationally arrange the time and area of high-intensity sports training, and carry out new-style sports training activities to ensure the sustainable development of high-intensity sports training behavior. Therefore, prevention and control of air pollution, scientific training arrangements have become a common concern. The purpose of this paper is to introduce the influence of smog pollution on the effect of intensive sports training and the countermeasures to prevent air pollution, so as to provide reasonable suggestions for better selection of training time, place and mode.